Nurses’ knowledge and practice in relation to peripheral intravenous catheter care - Ho, Siew Eng; Liew, LS; Tang, WS (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Peripheral Intravenous Catheters (PIC) are widely used. Nurses are required to possess appropriate knowledge and practice. The present study aimed to determine nurses' knowledge and practice towards care of PIC. A cross-sectional descriptive study was conducted and 84 respondents participated in the study. A 26-item questionnaire comprising 11 items on knowledge and 15 items related to nursing practice was adapted and modified. The findings reported higher mean score from specialty unit respondents, with knowledge (M = 49.19, SD = 3.44) and practice (M = 66.38, SD = 5.15), compared to medical surgical wards with knowledge (M = 46.25, SD = 4.68) and practice (M = 63.17, SD = 4.63) towards the care of PIC, which was significant (p value = 0.010 and p value = 0.009, respectively). The study indicated a higher mean score of charge nurse respondents as compared with registered nurse with knowledge (M = 49.68, SD = 3.23); (M = 46.20, SD = 4.62) and practice (M = 67.11, SD = 4.84); (M = 63.06, SD = 4.61), which was significant (p value = 0.003 and p value = 0.001, respectively). There were no significant differences between respondents’ education qualification towards care of PIC with p > 0.05. However, the findings reported that respondents who possessed Bachelor of Nursing were deemed to score slightly higher in their knowledge and practice towards the care of PIC. In conclusion, the specialty unit and charge nurse respondents were deemed to possess better knowledge and practice towards the care of PIC in the hospital.